Manajemen Keuangan Keluarga: Sosialisasi Peningkatan Kamanpuan Ibu Rumah Tangga dalam Mengelola Keuangan Keluarga di Desa Rawang Kota Pariaman - ive, Arivetullatif arive (Institut Agama Islam Sumatera Barat, 2023)
This service aims to provide knowledge and understanding to housewives in managing family finances. This needs to be done because of the development of very easy transaction methods so that family members can easily spend their money. This condition will affect the finances of families who have limited income. If this is allowed to continue, it can result in family conflict, the emergence of debt, lack of peace and family welfare. Service is carried out in the form of socialization, delivery of material, discussions and consultations. The targets for this socialization are housewives in Rawang Village, Central Pariaman District, Pariaman City. The socialization was carried out for 1 day and was expected to provide participants with an overview of the ways and importance of managing family finances.